Impact of the T2-weighted axial oblique MRI sequence in the assessment of peroneal tendons. Issue 8 (August 2020) - Gorelik, N.; Boily, M.; Lafrenière, A.-S.; Chari, B.; Powell, T.; Reinhold, C.; Jaffer, R.
Abstract : AIM: To define the role of the T2-weighted axial oblique sequence for the magnetic resonance imaging (MRI) assessment of peroneal tendon pathologies. MATERIALS AND METHODS: Two radiologists interpreted 180 ankle MRI examinations using standard sequences alone and then in combination with an axial oblique sequence. The readers indicated how likely a peroneal pathology was present using a five-level confidence scale. Diagnostic confidence, interobserver agreement, and clinical correlation were compared. Changes in diagnosis were recorded. RESULTS: For both readers, the diagnostic confidence was significantly higher using the axial oblique sequence for tendinosis and inframalleolar tenosynovitis for both tendons and for peroneus brevis partial and longitudinal split tears ( p <0.001). For reader 1, the diagnostic confidence was also higher using the axial oblique sequence for peroneus longus partial tears ( p =0.007). Changes in diagnosis were seen for tendinosis and tenosynovitis of both tendons and for peroneus brevis partial and longitudinal split tears in 0.6–10.8% of cases. Inter-rater reliability was significantly higher with the axial oblique sequence for the diagnosis of tendinosis, inframalleolar tenosynovitis, and partial tear for both tendons, and for peroneus brevis longitudinal split tear. Amongst 105 examinations with clinical information, peroneal pathologies were most frequently diagnosed as present in cases with lateral symptoms (17% versus 14%) and absent in cases without lateral symptoms (92% versus 86%) on the axial oblique sequence. CONCLUSION: The axial oblique sequence for the assessment of peroneal tendons allows for higher diagnostic confidence, inter-rater reliability, and clinical correlation and can lead to changes in diagnosis. Highlights: Axial oblique MR imaging of peroneal tendons improves diagnostic confidence. Inter-rater reliability is higher using the axial oblique MR plane for peroneal tendons. Axial oblique MR imaging of peroneal tendons enhances clinical correlation. Imaging peroneal tendons using the axial oblique plane can change the diagnosis.